The Impact of Social Media on Brand Equity : A Quantitative Study - Qian, Xiaojie (2011)
The development of social media poses tremendous impact on brand equity. Yet, systematic studies regarding how social media impacts brand equity is limited. As a result, managers and executives cannot make full use of the branding opportunities or mitigate risks. This paper is devoted to closing this gap. As the major reason why many executives are reluctant or unable to develop effective social media strategies is due to a lack of understanding about it, thus this paper illustrates in detail what social media is. In order to find out how social media impacts brand equity, a quantitative research is conducted to study brand equity factors based on Aaker’s brand equity model, find out each factor’s individual contribution to brand equity and social media’s impact on those individual factors. A clear understanding of how social media impacts brand equity is formed at the end of the research. Based on these insightful findings, recommendations are provided for organizations with a vision to enhance brand equity.